PENGGUNAAN MEDIA KINCIR PERKALIAN PADA MATERI KONSEP PERKALIAN DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS III SDN 21 LIMBOTO - Tutisna Tutisna; Herson Anwar; Febry Rizki Susanti Kalaka (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2025)
AbstractThis study aims to determine the use of multiplication wheel media in improving mathematics learning outcomes of third-grade students of SDN 21 Limboto on the concept of multiplication. The type of research used is classroom action research. The subjects in this study were 1 class teacher and 25 third-grade students and the object of this study was the use of multiplication wheel media to improve mathematics learning outcomes. The results of the study showed an increase before the action was carried out, student learning outcomes only reached 28%, after being given the first cycle action it increased to 52%. After the action was carried out in the first cycle, there was an increase in student learning outcomes to 52%, although there were still some students who had not reached the KKM. This increase shows that the use of multiplication wheel media began to have a positive impact on student understanding. Then in the second cycle, after improvements were made in the learning process, student learning outcomes increased significantly to 96%, with only 1 student who had not reached the KKM. These results indicate that the use of multiplication wheel media is able to improve students' understanding of the concept of multiplication in a concrete, interesting, and fun way.Keywords: Learning Outcomes, Multiplication Wheel Media, Mathematics, Multiplication Concept MaterialAbstrakPenelitian ini bertujuan untuk mengetahui penggunaan media kincir perkalian dalam meningkatkan hasil belajar matematika siswa kelas III SDN 21 Limboto pada materi konsep perkalian. Jenis penelitian yang digunakan penelitian tindakan kelas. Subjek dalam penelitian ini adalah 1 orang guru kelas dan 25 orang siswa kelas III dan objek Objek dalam penelitian ini adalah Penggunaan kincir perkalian untuk meningkatkan hasil belajar matematika. Hasil penelitian menunjukkan terjadi peningkatan sebelum dilakukan tindakan, hasil belajar peserta didik hanya mencapai 28%, setelah diberikan tindakan siklus I meningkat menjadi 52%. Setelah dilakukan tindakan pada siklus I, terjadi peningkatan hasil belajar peserta didik menjadi 52%, meskipun masih terdapat beberapa siswa yang belum mencapai KKM. Peningkatan ini menunjukkan bahwa penggunaan media kincir perkalian mulai memberikan dampak positif terhadap pemahaman siswa. Kemudian pada siklus II, setelah dilakukan perbaikan dalam proses pembelajaran, hasil belajar peserta didik meningkat secara signifikan menjadi 96%, dengan hanya 1 orang siswa yang belum mencapai KKM. Hasil ini menunjukkan bahwa penggunaan media kincir perkalian mampu meningkatkan pemahaman siswa terhadap konsep perkalian secara konkret, menarik, dan menyenangkan. Kata Kunci: Hasil Belajar, Media Kincir Perkalian, Matematika, Materi Konsep Perkalian